Improving Vocabulary Mastery and Reading Comprehension of Eighth Grade Students of SMPN 18 Bengkulu through Morphological Awareness Instruction - Ediah Yusti Mulyansari (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2019)
The purpose of this study was to find out whether or not Morphological Awareness Instruction could improve students’ vocabulary mastery and reading comprehension. This study also aimed to find out the students’ perception concerning the use of Morphological Awareness Instruction. A true experimental research method was applied to achieve the goal. The sample of this study was sixty students of SMPN 18 Kota Bengkulu which were chosen by using two stages of random sampling. To collect the data,a set of questionnaire and tests were used. Independent sample t-test was applied in analyzing the data. The results showed that (1) Morphological Awareness Instruction significantly improved students’ vocabulary mastery; (2) Morphological Awareness Instruction significantly improved students’ reading comprehension, and (3) there were positive perceptions of the students toward the use of Morphological Awareness Instruction in learning vocabulary and reading. Key words: Morphological Awareness Instruction, vocabulary mastery, reading comprehension.